Analysis of evaluating startups methods by a venture fund - E. S. Smolina; A. A. Polovinkina (Вестник университета)
The article contains research results of the economic indicators of evaluation for a project applying for venture financing. The main groups of indicators that are commonly used by venture fund’s experts to evaluate startups are analyzed; their main disadvantages are identified and systematized. Methods of comparison, general scientific methods of analysis and synthesis, induction and deduction were used in the study. Materials of the Venture Fund of the Samara region became the empirical basis for the study. Based on the study results of the practice of this fund when pre-invest evaluating startups, it’s possible to identify the presence of certain problems and extrapolate them to activities of other similar venture funds. The identification and systematization of pre-invest evaluation problems of startups that was carried out within the framework of this study will form the basis for further development of methodological tools for analyzing economic and financial prospects of innovative startups.